HOST STATUS OF CRISPY-LEAF LETTUCE CULTIVARS TO ROOT-KNOT NEMATODES - Franchin Sgorlon, Luis Fernando [UNESP]; Costa Silva, Edgard Henrique [UNESP]; Soares, Renato Silva [UNESP]; Borges, Heloisa Oliveira [UNESP]; Martins Diniz, Guilherme Matos [UNESP]; Braz, Leila Trevisan [UNESP]; Martins Soares, Pedro Luiz [UNESP] (Univ Federal Uberlandia, 2018)
Lettuce is the main leafy vegetable grown in the world, being the crispy-leaf lettuce type predominant. With consecutive cultivation in the same area, several factors may impair yield, highlighting the damage caused by root-knot nematodes, Meloidogyne spp. This study aimed at evaluating the reaction of twenty crispy-leaf lettuce cultivars to Meloidogyne incognita race 3, M. javanica and M. enterolobii. Three experiments were conducted, one for each nematode species. The experiments were carried out in a greenhouse, in pots with sterilized substrate. The design was completely randomized with five replications. Seedlings were inoculated with 1.000 eggs and second-stage juveniles of nematode per pot, on the day of transplantation of seedlings. The tomato 'Rutgers' was used as inoculum viability control for each specie tested. The variables evaluated were: reproduction factor (FR), total number of eggs and second-stage juveniles (NTOJ) and number of eggs and second-stage juveniles per gram of root (NOJGR), 60 days after inoculation. The results showed that the cultivars Veronica, Grand Rapids and Crespa para Verao are resistant to the three nematode species. The cultivars Thais, SRV 2005 and Marisa are resistant to M. incognita race 3 and M. javanica. The cultivar Black Seed Simpson is resistant to M. enterolobii. The cultivars Vanda and Monica SF 31 are resistant to M. incognita race 3. The cultivars Crespa, Rubia, Cinderela and Veneranda are resistant to M. javanica.
Keywords: Lactuca sativa L.; Meloidogyne spp.; Reproduction factor; Plant resistance